COIL AND THE DEVELOPMENT OF SOFT SKILLS IN VIRTUAL INTERNATIONALIZATION CONTEXTS: AN EXPLORATORY REVIEW - Acevedo, Jesus Enrique Reyes; Macahuachi, María Elena Tello; Murrieta, Henry Armas; Torres, Yuli Novak Ormeño (Seven Editora, 2026)
This study aims to analyze the scientific evidence regarding the implementation of Collaborative Online International Learning (COIL) and its impact on the development of soft skills in virtual internationalization contexts in higher education. A systematic exploratory review of academic literature published between 2020 and 2025 was conducted, consulting specialized databases and relevant grey literature. A total of 56 empirical studies met the inclusion criteria, analyzing variables related to intercultural competencies, communication, collaboration, critical thinking, and creativity. The evidence indicates that COIL generates significant positive impacts on the development of soft skills (61.8% positive outcomes). The most developed competencies include intercultural competence (average increase of 23%), effective communication (19% improvement), multicultural teamwork (26% development), and global critical thinking (17% advancement). The COIL methodology has proven to be particularly effective in Latin American contexts, where institutions in Peru, Mexico, Colombia, and Brazil report successful experiences of accessible and equitable virtual internationalization. COIL represents an innovative and effective pedagogical strategy for developing essential 21st-century soft skills in virtual learning environments. Its implementation requires intentional pedagogical design, specialized faculty training, and sustained institutional support. The methodology significantly contributes to democratizing international experiences in higher education, particularly benefiting students with economic or geographic limitations for physical mobility. DOI: https://doi.org/10.56238/sevened2026.008-079